2003
DOI: 10.1021/la0267948
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterns of Chemisorbed Cell Adhesion-Repellent Films Using Oxygen Plasma Etching and Elastomeric Masks

Abstract: Cellular micropatterning has become an important tool to precisely design cell-to-substrate attachment for cell biology studies, tissue engineering, cell-based biosensors, biological assays, and drug screens. This paper describes a new technique for micropatterning of cells that is based on the use of oxygen plasma as a patterning tool. The technique consists of (1) homogeneously grafting a glass substrate with a protein-repellent interpenetrating polymeric network (IPN) of poly(acrylamide) and poly(ethylenegl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 28 publications
3
129
0
Order By: Relevance
“…We cultured myogenic cells (C2C12 cell line) on microtracks of physisorbed fibronectin or Matrigel™ surrounded by protein-repellent PEG IPN. 28 PEG IPNs repelled cell adhesion and spread robustly over a long term (>4 weeks; we have not determined the upper value). To produce cell-adhesive tracks alternating with IPNs, we first homogeneously grafted PEG IPNs onto glass substrates and then used PDMS microchannels to selectively remove IPNs with oxygen plasma and to deposit ECM proteins onto etched tracks.…”
Section: Micropatterns Of Skeletal Myoblasts Andmentioning
confidence: 86%
See 3 more Smart Citations
“…We cultured myogenic cells (C2C12 cell line) on microtracks of physisorbed fibronectin or Matrigel™ surrounded by protein-repellent PEG IPN. 28 PEG IPNs repelled cell adhesion and spread robustly over a long term (>4 weeks; we have not determined the upper value). To produce cell-adhesive tracks alternating with IPNs, we first homogeneously grafted PEG IPNs onto glass substrates and then used PDMS microchannels to selectively remove IPNs with oxygen plasma and to deposit ECM proteins onto etched tracks.…”
Section: Micropatterns Of Skeletal Myoblasts Andmentioning
confidence: 86%
“…The pattern was created by selective etching of a homogeneous PEG IPN layer through a PDMS stencil. 28 When constrained to this pattern for long periods of time (Fig. 5C, 21 days), the neurons will eventually reach to neighboring islands and join their axons in bundles.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Tourovskaia et al have reported a method for generating cellular patterns on substrates coated with interpenetrating polymeric network (IPN) of poly(acrylamide) and poly(ethyleneglycol) film by patterned etching with oxygen plasma. 18 Although this method was successful in generating cell-adhesive areas by removing cell non-adhesive IPN film (19 nm thick), 19 it required approximately 15 min of repeated exposure to plasma. This limited the smallest feature to 15 mm because the elastomeric mask was heated and distorted during plasma treatment.…”
Section: Introductionmentioning
confidence: 99%